Penatalaksanaan Fisioterapi Pada Gangguan Fungsional Wrist Dan Hand Akibat Carpal Tunnel Syndrome Dengan Teknik Tendon Gliding Exercise Dan Self Neural Mobilization - Meida Hayati Meida Hayati; Arfian Hamzah; Yulisha Eva Oktaviani (Politeknik Unggulan Kalimantan, 2023)
The increasing prevalence of CTS cases from every year, especially in Banjarmasin, has led the authors to be interested in conducting research on